A Golgi-targeting fluorescent probe for labile Fe(ii) to reveal an abnormal cellular iron distribution induced by dysfunction of VPS35. Issue 5 (30th November 2018) - Hirayama, Tasuku; Inden, Masatoshi; Tsuboi, Hitomi; Niwa, Masato; Uchida, Yasuhiro; Naka, Yuki; Hozumi, Isao; Nagasawa, Hideko
Abstract : Fluctuation of labile Fe(ii ) at Golgi apparatus was specifically detected by a new fluorescent probe. Abstract : Iron is involved in numerous physiologically essential processes in our body. However, excessive iron is a pathogenic factor in neurodegenerative diseases, causing aberrant oxidative stress. Divalent metal transporter 1 (DMT1) acts as a primary transporter of Fe(ii ) ions. The intracellular delivery of DMT1 toward the cellular membrane via the trans-Golgi network during the endocytotic process is partially regulated by a retromer-mediated protein-sorting system comprising vacuolar protein-sorting proteins (VPSs). Thus, together with DMT1, the Golgi-apparatus acts as a hub organelle in the delivery system for intracellular Fe(ii ) ions. Dysfunction of the VPS-relevant protein sorting system can induce the abnormal delivery of DMT1 toward lysosomes concomitantly with Fe(ii ) ions. To explore this issue, we developed a fluorescent probe, Gol-SiRhoNox, for the Golgi-specific detection of Fe(ii ) ions by integrating our original N -oxide-based Fe(ii )-specific chemical switch, a new Golgi-localizable chemical motif, and polarity-sensitive fluorogenic scaffold. Our synchronous imaging study using Gol-SiRhoNox and LysoRhoNox, a previously developed fluorescent probe for lysosomal Fe(ii ), revealed that the intracellular distribution balance of Fe(ii ) ions between the Golgi apparatus and lysosomes is normally Golgi-dominant, whereas the lysosome-specific elevation of Fe(ii ) ions was observed in cells with induced dysfunction of VPS35, a member of the retromer complex. Treatment of cells with dysfunctional VPS35 with R55, a molecular chaperone, resulted in the restoration of the subcellular distribution of Fe(ii ) ions to the Golgi-dominant state. These results indicate that the impairment of the DMT1 traffic machinery affects subcellular iron homeostasis, promoting Fe(ii ) leakage at the Golgi and lysosomal accumulation of Fe(ii ) through missorting of DMT1.